Some clinical field studies on the effect of ceftiofour sodium in naturally E-Coli-Infected camels - Bogzil, Alsadek H.; Shams, Gamal; El-kaseh, Rafi M.; Malhat , Seham (Al-Mukhtar Journal of Sciences, 2012)
The present investigation was conducted on twenty camels, fifteen of them were naturally- infected with E-coli microorganisms, the other five were apparently healthy. They were divided into two groups. The first group (5- camels) were served as a control one (non-infected, non treated). The second group (15- camels) were naturally infected with E-Coli and treated subcutaneously with ceftiofur sodium in a dose 5.0mg /kg.b-wt for three successive days. Two blood samples (one with anticoagulant and the other without anticoagulant) were collected from healthy camels and the naturally E-Coli-infected camels (before treatment and one-week post treatment) for hematological and biochemical determination. E-Coli-infected camels showed significant decrease in erythrocytic counts, Hb conc and PCV. It showed leucopenia, neutrapenia, lumphopenia associated with monocytosis in comparison to the control camels. It also, revealed lowering values of calcium, phosphorus, potassium, sodium, glucose, total serum protein, while GGt, ALP, serum urea and creatinine showed a higher values in comparison to control camels. All parameters and the signs of infected camels were improved towards the normal levels one week after treatment with ceftiofur sodium. The goal of our investigation was to evaluate the efficacy of ceftiofur sodium in naturally infected camels by determining the hematological and biochemical parameters of healthy and infected animals (pre and post treatment with ceftiofur sodium).